MAVEN observations of magnetic flux ropes with a strong field amplitude in the Martian magnetosheath during the ICME passage on 8 March 2015 - Takuya Hara; Janet G. Luhmann; Jasper S. Halekas; Jared R. Espley; Kanako Seki; David A. Brain; Hiroshi Hasegawa; James P. McFadden; David L. Mitchell; Christian Mazelle; Yuki Harada; Roberto Livi; et al. (Geophysical Research Letters)
Abstract We present initial results of strong field amplitude flux ropes observed by Mars Atmosphere and Volatile EvolutioN (MAVEN) mission around Mars during the interplanetary coronal mass ejection (ICME) passage on 8 March 2015. The observed durations were shorter than 5 s and the magnetic field magnitudes peaked above 80 nT, which is a few times stronger than those usually seen in the magnetosheath barrier. These are the first unique observations that MAVEN detected such flux ropes with a strong field at high altitudes (>5000 km). Across these structures, MAVEN coincidentally measured planetary heavy ions with energies higher than a few keV. The spatial properties inferred from the Grad‐Shafranov equation suggest that the speed of the structure can be estimated at least an order of magnitude faster than those previously reported quiet‐time counterparts. Hence, the space weather event like the ICME passage can be responsible for generating the observed strong field, fast‐traveling flux ropes.